Bromodomain-containing factor GTE4 regulates Arabidopsis immune response - Qin Zhou; Yingnan Sun; Xiwang Zhao; Yue Yu; Weijia Cheng; Li Lu; Zhaohui Chu; Xiangsong Chen (BMC Biology, 2022)
Abstract Background Plants are continuously challenged with biotic stress from environmental pathogens, and precise regulation of defense responses is critical for plant survival. Defense systems require considerable amounts of energy and resources, impairing plant growth, and plant hormones controlling transcriptional regulation play essential roles in establishing the appropriate balance between defense response to pathogens and growth. Chromatin regulators modulating gene transcription are broadly involved in regulating stress-responsive genes. However, which chromatin factors are involved in coordinating hormone signaling and immune responses in plants, and their functional mechanisms, remains unclear. Here, we identified a role of bromodomain-containing protein GTE4 in negatively regulating defense responses in Arabidopsis thaliana. Results GTE4 mainly functions as activator of gene expression upon infection with Pseudomonas syringe. Genome-wide profiling of GTE4 occupancy shows that GTE4 tends to bind to active genes, including ribosome biogenesis related genes and maintains their high expression levels during pathogen infection. However, GTE4 is also able to repress gene expression. GTE4 binds to and represses jasmonate biosynthesis gene OPR3. Disruption of GTE4 results in overaccumulation of jasmonic acid (JA) and enhanced JA-responsive gene expression. Unexpectedly, over-accumulated JA content in gte4 mutant is coupled with downregulation of JA-mediated immune defense genes and upregulation of salicylic acid (SA)-mediated immune defense genes, and enhanced resistance to Pseudomonas, likely through a noncanonical pathway. Conclusions Overall, we identified a new role of the chromatin factor GTE4 as negative regulator of plant immune response through inhibition of JA biosynthesis, which in turn noncanonically activates the defense system against Pseudomonas. These findings provide new knowledge of chromatic regulation of plant hormone signaling during defense responses.